Pengembangan Sistem Informasi Pelayanan Kependudukan di Kecamatan Cibeunying Kidul - Nana Sujana; Nur Azizah; Hendriady de Keizer (Jurnal Accounting Information System (AIMS), 2021)
Cibeunying Kidul District is a government agency that has implemented a computerized population data recording system in its work, such as at the time of applying for a KK and KTP, only some still use the manual method, namely when applying for incoming and outgoing moving letters. The process of recording data manually in a ledger provided directly by service officers. This of course makes time inefficient, because the data recording process takes a long time.The Population Service Information System Design Solution is quite effective and efficient in the process of recording data in the KK registration book, KTP, Transfer Letter and Letter of Moving Out. It is hoped that after implementing this solution service officers can undergo a fast, precise, and accurate community service process.